THE ROLE OF GOOD CORPORATE GOVERNANCE AND INFORMATION AND COMMUNICATION TECHNOLOGY IN IMPROVING SERVICE QUALITY THROUGH SERVICE EFFICIENCY: EVIDENCE FROM PT PLN (PERSERO) UP3 BERAU - Ikrarda Tegar Pambudi; Umi Muawanah; FX Bhakti Hendrakusuma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The development of the Society 5.0 era requires State-Owned Enterprises (SOEs) to improve public service quality amid increasing technological disruption and rising public expectations. However, public service delivery in SOEs continues to face strategic challenges, such as complaints regarding delays, inefficiency, procedural uncertainty, and low responsiveness. This study aims to examine the effects of Good Corporate Governance and Information and Communication Technology on service quality through service efficiency at PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan Berau. The study population consisted of 72 employees, and 69 valid responses were obtained using a census (saturated sampling) method. Data were collected through structured five-point Likert questionnaires and organizational documents, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that GCG significantly improves both service quality and service efficiency, and indirectly enhances service quality through service efficiency. ICT significantly influences service efficiency and indirectly improves service quality, although its direct effect on service quality is not significant. Service efficiency was found to mediate the relationships between GCG and ICT with service quality. These findings highlight the importance of implementing GCG principles and integrating ICT to streamline processes, enhance efficiency, and ultimately improve the quality of public services in SOEs.